2016
DOI: 10.1111/sji.12408
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Interleukin‐17 Restrains the Development of Acute Lung Injury

Abstract: The acute respiratory distress syndrome (ARDS), a clinical complication of severe acute lung injury (ALI) in humans, is a leading cause of morbidity and mortality in critically ill patients. Here, we explored the association between IL-17 and development of ALI using LPS-induced murine model. We found that IL-17 level was elevated in bronchoalveolar lavage (BAL) fluid of ALI mice. Upregulation of IL-17 resulted in increased severity of ALI as evidenced by decreased body weight and survival rate, elevated level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 38 publications
(44 reference statements)
3
34
0
Order By: Relevance
“…IL-17 plays an important role in leukocyte infiltration. Studies have shown reduced G-CSF secretion in IL-17R-/- mice and that these mice were protected against ARDS [42,43]. In this study, aerosol exposure resulted in attenuated levels of MCP-1, RANTES, IL-17A, IL12p40, and IL-4 in BALF (Figure 6D-H).…”
Section: Resultssupporting
confidence: 58%
“…IL-17 plays an important role in leukocyte infiltration. Studies have shown reduced G-CSF secretion in IL-17R-/- mice and that these mice were protected against ARDS [42,43]. In this study, aerosol exposure resulted in attenuated levels of MCP-1, RANTES, IL-17A, IL12p40, and IL-4 in BALF (Figure 6D-H).…”
Section: Resultssupporting
confidence: 58%
“…Here, we argue that targeting IL-17 is immunologically plausible as a strategy to prevent acute respiratory distress syndrome (ARDS) in coronavirus disease 2019 (COVID-19) and discuss why we think that a clinical trial of a drug in this class could be a logical addition to the effort to find effective therapies. study, mice genetically deficient in IL-17 or those that received anti-IL-17 antibodies demonstrated improved survival, less lung infiltration and better lung pathology scores following LPS challenge 8 .…”
mentioning
confidence: 86%
“…The release of many cytokine and the regulation of inflammatory pathways are regulated by some transcription factors such as NF-κB, thus, any changes in their structure and expression might influence cytokine production and ARDS progress [61]. Since increased IL-17 may serve as a biomarker to indicate the severity of ARDS in patients with sepsis-induced ARDS [62], researchers have estimated the IL-17 (rs763780, rs2275913, and rs8193036) and NF-κB1 (rs3774934) polymorphisms in a Chinese population that were associated with ARDS prediction and prognosis [63]. This conclusion further shows that the detection of related gene expression and variants has an important role in the prediction and prevention of the occurrence and development of ARDS.…”
Section: Resultsmentioning
confidence: 99%